Research on Starting Control Method of New-Energy Vehicle Based on State Machine - Wu, Yezhen; Xu, Yuliang; Zhou, Jianwei; Wang, Zhen; Wang, Haopeng (Energies (Basel), 2020)
In order to improve the starting smoothness of new-energy vehicles under multiple working conditions and meet the driving intention better, and to make the control strategy have high portability and integration, a starting control method for vehicle based on state machine is designed. Based on inclination, starting of vehicle is divided into three working conditions: flat road, slight slope and steep slope. The method of vehicle starting control is designed, which includes five control states: default state control, torque pre-loading control, anti-rollback control, pedal control and PI (Proportion-Intergral) creep control. The simulation is carried out under the conditions of flat road, slight slope and steep slope. In terms of flat road and light slope, the vehicle travels below 3 km/h according to the driver’s intention, the speed is stable at 8 km/h during the creeping control phase and the jerk is lower than 5 m/s3. In terms of steep slope, the speed is controlled at 0 km/h basically and the 10 s-rollback distance is less than 0.04 m. The results show that the strategy can fully meet the driver’s intention with lower jerk, better dynamic and stability, and the method can achieve the demand of new-energy vehicle starting control.